Rekonstrukcija ozemelj prazgodovinskih skupnosti na prostoru severnega in srednjega Velebita z uporabo GIS-ov - Glavaš, Vedrana (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
A method for reconstructing prehistoric territories implementing the geographic information systems (GIS) is presented in this article. We focused our research on Iron Age communities of northern and central Velebit Mountain (Croatia), but traces of their territorial extent are very scarce or nonexistent. Territories of the communities in question were modeled using GIS according to the relief characteristics and the time scale of a two-hour walk from the central hill forts using Tobler's Hiking Equation.
Keywords: Croatia; geografija; geografski informacijski sistemi; geography; Hrvaška; naselja; prazgodovina; Velebit; železna doba